Alterations in atrial electrogram amplitude as steady sinus rhythm transitions to paroxysmal atrial fibrillation during continuous monitoring in patients with implantable cardiac devices: Insights from the IMPACT study. (22nd March 2021) - Kantharia, Bharat K.; Lip, Gregory Y. H.; Martin, David T.
Abstract: Objectives: We aimed to evaluate whether device measured amplitudes of atrial electrogram (AEGM) would change when measured in sinus rhythm (SR) transitioning to paroxysmal atrial fibrillation (AF) from previous steady SR, and significance of such change. Methods: From the IMPACT trial's database we selected two groups; (A) those who developed AF ( n  = 164), and (B) propensity‐matched control ( n  = 459) who stayed in SR during continuous Home Monitoring (HM) to compare AEGMs amplitudes at baseline SR and transition phase. Results: During 420.0 ± 349.2 days (mean ± SD) from first postenrollment HM transmission to AF event transmission in Group A, and corresponding 515.3 ± 407.0 days in Group B, baseline and transition AEGM amplitude were 2.88 ± 1.146 and 2.74 ± 1.186 mV, respectively, for Group A ( p  = .1), and 2.88 ± 1.155 and 2.79 ± 1.145, respectively, for Group B ( p  < .005). Comparison of differences of AEGM amplitude, 0.14 ± 1.072 mV in Group A and 0.09 ± 0.893 mV in Group B were insignificant ( p  = .3). Age, sex, and hypertension identified as confounders had no association to AEGM changes ( p  = NS). Conclusions: Independent of age, sex, and hypertension, AEGMs amplitudes decline over a long period of time in patients with defibrillators and substrate for AF. The significance of such change remains unclear as it occurs whether patients develop AF or not, but raises a possibility of progressive atrial myopathy that patients with substrate for AF may be predisposed to.